(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
During the enrollment period, Admission to Bestlink College of the Philippines encountered a lot of difficulties since thousands of students went to the admission office for the requirements needed to enroll. It was done manually, which consumed a lot of time for the students and the admission officers. Also, it burdens the admission officers to manually review the applications of thousands of students, and it causes delays in updating students’ records and the students themselves. Because of this, the project team came up with the idea of creating an Online enrollment System that helps the institution, admission, and students as well. The objective of this system is to keep track of and secure student records, save money, and have an easier and faster transaction during the enrollment process. As a result, the client gave feedback and found the system very good in terms of its functionality, reliability, usability, efficiency, maintainability, portability, and only good concerning its efficiency. It shows that the system provides a high level of quality and requires minimal rectifications for improvement. Also, it means the system satisfies the client and the requirements are met. The system has finally been developed and implemented into a new approach with the help of the agile methodology, meeting with the client, client testing, gathering information, and the ideas of the project team. It is an easier process for the school, admission, and students during enrollment. Overall, an online enrollment system for school management systems improves efficiency, accessibility, and communication between all stakeholders involved in the education process.